APLIKASI PENDEKATAN TEMATIS UNTUK PEMBINAAN KOMPETENSI KOMUNIKATIF BAHASA INDONESIA PADA SISWA SLTP - Andayani, Andayani (PAEDAGOGIA, 2008)
This research aims to describe the increasing of the students' Indonesiancommunicative competence and the collaboration between the lecturer and teacher inestablishing the students' Indonesian communicative competence. This research wasconducted using qualitative-method. The sources of data were collected from informantsand were determined through criterion-based-selection. The data were taken throughdeep interview and direct observation. Then they were analyzed by interactive-methodand served in description-based on domain analysis. This research concludes that theteachers who have positive perception can increase the students' Indonesian communicativecompetence. The effective interactions in the Indonesian teaching in thisresearch is multi directions and students' Indonesian communicative competence wasshown by grammatical competence, sociolinguistic competence, and discourse competence.